Embracing technology? Health and Social Care professionals' attitudes to the deployment of e-Health initiatives in elder care services in Catalonia and Ireland, - Lolich, Luciana; Timonen, Virpi (My University, 2019)
Professionals in both regions have a positive attitude towards the use of e-health as a supportive tool. Technology is seen as way of reducing administrative burden and improving information exchange. Professionals expressed concerns about technology as a substitute for face-to-face contact. Training on ICT and change management procedures should accompany e-health initiatives. Lack of system integration between different providers is a major barrier to meaningful use of technology in care services.
PUBLISHED
Keywords: Ireland; Catalonia; eHealth; Technology enablers; Barriers to technology; Ageing; Digital Engagement; Digital Humanities; Making Ireland; OLDER PEOPLE